Inclusive MOOCs as an antidote to stereotype threat in education: state of the art and future directions - Katharina-Maria Illgen; Lorena Göritz; Daniel Stattkus; Jan Heinrich Beinke; Oliver Thomas (Discover Education)
Abstract This study examines the potential of inclusive design in Massive Open Online Courses (MOOCs) to address the impact of stereotype threat, a significant barrier encountered by underrepresented groups, particularly in STEM education. As online learning opportunities grow, the demographic composition of course participants frequently does not reflect broader societal diversity, with women and racial minorities remaining underrepresented in fields such as computer science and mathematics. This phenomenon reflects societal stereotypes that shape perceptions and constrain study choices. MOOCs, given their global reach, flexible structure, and often anonymous nature, have the potential to challenge these stereotypes when designed inclusively. This work synthesizes existing research and provides a broader perspective on strategies for fostering inclusivity in MOOCs through a systematic literature review, focusing on methods to counteract stereotype threat. The aim is to propose practical solutions for inclusive course design to empower marginalized learners and promote equitable education, enhancing the representation of marginalized learners in both educational and professional spheres. Furthermore, the findings of this study indicate the necessity for further investigation into the design of inclusive MOOCs, providing a future research agenda. This work contributes to the academic discourse on the potential of MOOCs to foster an integrated approach toward inclusive digital transformation in education, thereby enabling supportive digital inclusive learning environments. Moreover, it is of significant societal and organizational relevance, particularly in promoting diversity within STEM fields and beyond and creating a more equitable future where learners can flourish, regardless of background or prevailing stereotypes.